Impacto del programa Albem para fomentar emociones positivas de alegría y orgullo en niños de tercer grado de primaria - Bernilla Meneses, Alberto (2022)
The study of emotions and their practical implications in the teaching of school classes is a pending issue in order to achieve deep learning, until pedagogy does not deal with the emotional education of its students, there will be no significant results. This research designed an emotional educational program focused on the emotional competencies of Bisquerra, this program aims to promote the positive emotions of joy and pride in third and fourth grade students, boys and girls between 8 and 10 years old. The research is experimental because an intervention was carried out on the students, and the results will be evaluated from a pre and a post test to analyze the impact generated. The sample was not chosen randomly and there was no control group, so it is a quasi-experiment. The sample consisted of 17 students from a private school in Arequipa, the instrument used was a questionnaire adapted from Oros (2014), which underwent a statistical validation analysis through a pilot test. The Albem educational program did not have a significant impact on the sample, after applying the 21 activities that compose it, the post test showed that there was no impact on the students. But the results of the pre and post test were located above the midpoint.